2020
DOI: 10.2991/jegh.k.200402.001
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Oseltamivir Prophylaxis in Influenza Outbreaks in Residential Aged Care

Mithilesh Dronavalli,
Heidi Lord,
Kate Alexander
et al.

Abstract: Influenza outbreaks in Aged Care Facilities (ACFs) can lead to hospitalizations and deaths. Influenza can spread rapidly through ACFs if precautionary measures are not taken. Along with influenza vaccination and precautionary hygiene measures, Oseltamivir Prophylaxis (OP) may be effective in reducing the attack rate of influenza by preventing new cases. A cohort study was carried out to investigate the effectiveness of OP use during influenza outbreaks in ACFs located within South Western Sydney Local Health D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 20 publications
(23 reference statements)
1
36
0
Order By: Relevance
“…Importantly, hospitalisations due to influenza outbreaks were significantly lower when ACFs used POCT, reducing the possibility by 43%. Although our study is small and observational, it is supported by a recent study that found antiviral prophylaxis prevented a high percentage of influenza cases during outbreaks, particularly in ACFs with high‐level care and dementia units 15 . This may be relevant to ACFs struggling to manage the threat of COVID‐19.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Importantly, hospitalisations due to influenza outbreaks were significantly lower when ACFs used POCT, reducing the possibility by 43%. Although our study is small and observational, it is supported by a recent study that found antiviral prophylaxis prevented a high percentage of influenza cases during outbreaks, particularly in ACFs with high‐level care and dementia units 15 . This may be relevant to ACFs struggling to manage the threat of COVID‐19.…”
Section: Discussionsupporting
confidence: 63%
“…NSW Health recommend antiviral treatment and prophylaxis (oseltamivir) as per the Commonwealth CDNA Guidelines. Although there are multiple recognised protocols across ACFs, all suggest the implementation of antivirals within 72 hours 15 . Despite some conflicting evidence on the effectiveness of antivirals use in ACFs, more data are emerging 14 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of antiviral drugs such as oseltamivir, which if taken within 48 hours after the initial symptoms, can reduce disease severity and influenza‐associated complications, 10 and studies have shown impact of using oseltamivir as prophylaxis in preventing and management of influenza in the residential care facilities 11‐13 . One study reported that oseltamivir prophylaxis reduces the influenza attack rate of 90% in residents during outbreaks, particularly in high care wards 11 . Furthermore, crowded living conditions and the frequent use of common rooms favour a rapid spread of respiratory infections.…”
Section: Introductionmentioning
confidence: 99%